TECHNOLOGY THE FIRE DETECTION SYSTEM ON THE RAILWAY LINE IS BASED ON IMAGE PROCESSING WITH THE COMPUTER VISION METHOD - Hilma Najya; Ari Purno Wahyu Wibowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The rail transportation system plays a role important as a medium of transportation for the movement of goods and people in large quantities and is one of the modes of cheap transportation, this transportation model evolved from a steam train until it evolves to become more sophisticated using electric and magnetic technology, trains system works well with support from several the first factor is human resources, supporting technology and facilities. The problem with the rail system is that damage to the rails can cause result in the transportation route being blocked and can cause a very fatal accident, Based on these problems, besides the feasibility of the rail system, rail maintenance is a very important key, the railroad track maintenance system is usually carried out periodically. The solution to handle this problem is to use a computer vision method by utilizing surveillance cameras or CCTV installed on railroad crossings able to detect damage, the detection of damage is categorized into a few types first is track damage, due to shifts, fires on rail lines and finally structural damage due to earthquakes or landslides in the railway line area, this technology has been applied to several developed countries. and can monitor a large area and can provide a quick response if a malfunction occurs, the system will be a smart monitoring system but doesn't replace the role of a railway officer but as a tool that will provide complete information where the location of the damage is so that prompt and more effective repair action can be taken.